2012
DOI: 10.3892/mco.2012.38
|View full text |Cite
|
Sign up to set email alerts
|

Histological profile and age at diagnosis of breast and ovarian tumors: A register-based study in Espirito Santo, Brazil

Abstract: Abstract. Breast and ovarian cancers are important public health problems in Brazil. However, in various locations in the Brazilian territory these types of cancer remain poorly characterized. Therefore, this study aimed to compare data collected from the Pathology Services of two Oncology Reference Hospitals in Espirito Santo state (Brazil) with the data in previous Brazilian studies. Histological type frequency and age at diagnosis of breast and ovarian tumors between 2001-2004 and 2009-2010 were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Several studies [15,21,22,23] revealed the relationship of expression between subtypes(ER, PR and HER2) with age. ER and PR-high expression were observed in females who were 50 or younger, [15,24] and in our study, too.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [15,21,22,23] revealed the relationship of expression between subtypes(ER, PR and HER2) with age. ER and PR-high expression were observed in females who were 50 or younger, [15,24] and in our study, too.…”
Section: Discussionmentioning
confidence: 99%